HUBUNGAN BUDAYA KERJA, GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA DALAM MENINGKATKAN KINERJA GURU DAN MUTU PENDIDIKAN DI SMP NEGERI 1 DAN SMP NEGERI 6 KOTABARU - Puspa Herliana; Helyna Riskawaty; Hendry Hermawan; Rizky Amelia (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
This study analyzes the relationship between work culture, leadership style, work motivation, and work discipline on teacher performance at SMP Negeri 1 and SMP Negeri 6 Kotabaru using a mixed-method approach. Quantitative analysis results show that work culture and work discipline do not have a significant effect on teacher performance, with p-values of 0.235 and 0.225, respectively. In contrast, leadership style and work motivation have significant effects, with p-values of 0.007 and 0.000, respectively. Qualitative analysis indicates that while work culture and work discipline do not have a direct impact, they remain important in supporting teacher performance. The simultaneous hypothesis suggests that all variables collectively influence teacher performance, although individual contributions from work culture and work discipline are not significant. This research provides insights for the development of more effective educational policies.